Mencari Format Ideal Teo-Ekologi dari Hubungan Antar Agama dan Sains - Baedhowi - (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2007)
This article attempts to describe the frame-works and approaches of science and religion. Although both of these disciplines are difference in gaining their main goals, they have not to be opposite in dichotomies. The oppositions of scientific and religious thought have become a secularist civilisation and have made some crisis. One of them is an ecological crisis. We can show relationship between science and religion in two models, both science and religion have difference methodology and approach, science and religion have same apparel or similar methodology and approach. In the last model, scientific and religious views can be harmonized to build a new perspective of theology. From these views, the writer tries to show, and to developed mutual dialogue and integration of science and religion and to explore the urgency or significant meaning of process theology as a new Theo-ecology, especially in Islamic thought.